2009
DOI: 10.1002/humu.20807
|View full text |Cite
|
Sign up to set email alerts
|

FOXL2mutations and genomic rearrangements in BPES

Abstract: The FOXL2 gene is one of 10 forkhead genes, the mutations of which lead to human developmental disorders, often with ocular manifestations. Mutations in FOXL2 are known to cause blepharophimosis syndrome (BPES), an autosomal dominant eyelid malformation associated (type I) or not (type II) with ovarian dysfunction, leading to premature ovarian failure (POF). In addition, a few mutations have been described in patients with isolated POF. Here, we review all currently described FOXL2 sequence variations and geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
104
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(112 citation statements)
references
References 86 publications
6
104
0
Order By: Relevance
“…23 So far, more than 100 different mutations have been described involving FOXL2, and pathogenic variants can be found in approximately 88% of cases. 24 The presence of other loci causing the syndrome also has been proposed, although a clear association is still lacking. 17,25,26 We performed molecular screening of FOXL2 in 16 patients to analyze specifically the LG phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 So far, more than 100 different mutations have been described involving FOXL2, and pathogenic variants can be found in approximately 88% of cases. 24 The presence of other loci causing the syndrome also has been proposed, although a clear association is still lacking. 17,25,26 We performed molecular screening of FOXL2 in 16 patients to analyze specifically the LG phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…32 The third missense mutation (c.313A>C), found in 2 related patients, is a novel pathogenic variant and causes the substitution of an asparagine for a histidine in the forkhead domain of FOXL2. 24 The remaining 4 mutations included 2 insertions, c.919_920insACCGCCGC and c.768-769insG, a nonsense mutation, c.370A>T, and a deletion, c.172_176delTCGTA. Only the first insertion has been described.…”
Section: Discussionmentioning
confidence: 99%
“…BPES patients represent an autosomal-dominant condition characterized by defects in eyelid development with (type I) or without (type II) premature ovarian failure (Fraser et al 1988;Crisponi et al 2001;De Baere et al 2005Raile et al 2005;Nallathambi et al 2007;Beysen et al 2009;Dipietromaria et al 2009;Méduri et al 2010). Within the ovary, FOXL2 has been shown to be essential for ovary development and function (Pisarska et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of the disorder is about 1:2500 live female births (Sybert & McCauley 2004). In women with 45,X karyotype, oocyte loss occurs in the early stages of meiotic prophase, resulting in gonadal dysgenesis and PA with Sedgwick & Boder (1991), Perheentupa (1996), Weinstein et al (2004), Fogli et al (2003Fogli et al ( , 2004, Beysen et al (2009) Zhao et al (2008a,b) elevated FSH levels since early childhood (Reynaud et al 2004, Fechner et al 2006. However, spontaneous menarche and pregnancy have been reported not only in patients with mosaic karyotype, but also in few nonmosaic 45,X women (Pasquino et al 1997, Cools et al 2004, Livadas et al 2005.…”
Section: Syndromic Poimentioning
confidence: 99%
“…More than 125 FOXL2 variants have been described in individuals with BPES types I and II, demonstrating that phenotypic features are caused by the pleiotropic effect of a single gene, rather than by a contiguous gene syndrome. Beysen et al (2009) recently reviewed a total of 106 unique intragenic FOXL2 mutations identified in 206 unrelated families with BPES of different ethnic origins. Detailed information on most FOXL2 mutations and on affected individuals or families with BPES was made available in the FOXL2 mutation database (http://users.ugent.be/ wdbeysen/foxl2).…”
Section: Blepharophimosis-ptosis-epicanthus Inversus Syndromementioning
confidence: 99%